Դիզայնի փիլիսոփայությունը - Լիլիթ Մելիքյան (ՀՀ ԳԱԱ հրատ.)
Հոդվածում բացահայտված են դիզայնի գեղագիտական էության փիլիսոփայական ընկալման հիմնահարցերը: В статье раскрыты проблемы философского восприятия эстетической сущности дизайна. This article reveals the issues related to the philosophical perception of the esthetical essence of design.
Keywords: Arts; Drawing; Design; Illustration; Culture and Cultural Processes; Fine Arts